(untitled) (REMUNOM, 2026)
Contemporary taxation has expanded its functions beyond revenue collection, increasingly acting as an instrument of economic and social regulation. In this context, the selective tax stands out as a mechanism of extrafiscality aimed at correcting negative externalities associated with the consumption of certain goods and services. This study aims to analyze the selective tax as an element of extrafiscality within the Brazilian tax system, examining its theoretical foundations, regulatory function and relevance in the context of contemporary public policies. To achieve this objective, a qualitative research approach was adopted, with an exploratory and descriptive design based on a literature review of recent scientific studies addressing tax extrafiscality, fiscal selectivity and economic regulation through taxation. The analysis of the selected literature indicates that the selective tax has significant potential to influence patterns of consumption and production, particularly when applied to products considered harmful to public health or the environment. The findings demonstrate that selective taxation may contribute to the mitigation of negative externalities, the promotion of public policies and the strengthening of state strategies aimed at sustainable development. It is concluded that the selective tax represents an important fiscal policy instrument in the contemporary context, enabling the tax system to operate not only as a revenue-generating mechanism but also as a tool for economic regulation and promotion of collective interests.